The Charismatic Leadership of the Madrasah Principal in Enhancing Students' Intrapersonal Intelligence - Rofiq Faudy Akbar; Dwi Arizqa Febrianti; Syafa Hidayatunni’mah (Journal of Educational Management Research, 2026)
This study aims to analyze the role of charismatic leadership in enhancing students’ intrapersonal intelligence within an Islamic educational setting. Grounded in Howard Gardner’s theory of multiple intelligences and Max Weber’s concept of charismatic authority, the research examines how a spiritual-educational leader influences students’ personal development. This study employed a qualitative field research design. Data were collected through observations, in-depth interviews, and documentation involving the principal, teachers, and students. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that charismatic leadership—characterized by integrity, effective communication, firmness in decision-making, empathy, and an inspirational vision—significantly contributes to the development of students’ intrapersonal intelligence. Students demonstrate improved self-awareness, emotional regulation, independence, and commitment to ethical and spiritual values. Nevertheless, challenges persist, particularly in fostering consistent emotional control and self-discipline among some students. The study implies that charismatic leadership plays a crucial role in integrating academic achievement with character formation. It offers theoretical contributions to leadership and educational studies and provides practical insights for Islamic educational institutions in promoting holistic student development.